Columnar Stacking of Partially Fluorinated [4]Helicenes: C−H⋅⋅⋅F Interactions Change the Stacking Orientation. Issue 8 (19th March 2020) - Suzuki, Risa; Uziie, Yuto; Fujiwara, Wataru; Katagiri, Hiroshi; Murase, Takashi
Abstract: The partial fluorination of polycyclic aromatic hydrocarbons often produces a layered crystal packing, where fluorinated aromatic surfaces are stacked over nonfluorinated aromatic surfaces. Herein, we report the synthesis and crystal packing of partially fluorinated [4]helicenes with steric congestion resulting from H and F atoms in the fjord region. F6 ‐[4]Helicene forms head‐to‐tail columnar stacks consisting of an alternate arrangement of perfluorinated and nonfluorinated naphthalene moieties. With decreasing fluorine content, aromatic stacking switched from arene−fluoroarene (Ar H −Ar F ) hetero‐stacking to Ar H −Ar H /Ar F −Ar F homo‐stacking with the help of intermolecular C−H⋅⋅⋅F contacts in the fjord region. As a result, head‐to‐head columnar stacks appear. Therefore, the conventional Ar H −Ar F stacking motif is not always applicable to F n ‐[4]helicenes with twisted π‐surfaces. Abstract : Switching the stacking orientation : Highly fluorinated [4]helicenes generated arene−fluoroarene (Ar H −Ar F ) stacks as usual, but were susceptible to short F⋅⋅⋅F contacts. In contrast, less‐fluorinated [4]helicenes used C−H⋅⋅⋅F interactions to replace weakened Ar H −Ar F hetero‐stacks with Ar H −Ar H /Ar F −Ar F homo‐stacks.